Antimony-free fireproof flame-retardant cable material as well as preparation method and application thereof

By combining chlorinated polyethylene and polyethylene with butadiene-based polymer in the cable material, and using components such as alkenyl ring triphosphazene to build a collaborative flame retardant system, the problem of degradation of cable materials in high temperature and high humidity environments is solved, and the excellent fire-retardant and mechanical properties of antimony-free cable materials are achieved.

CN119708716APending Publication Date: 2025-03-28JIANGSU DASHENG POLYMER
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411973931.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing cable materials are difficult to maintain stable operation in high temperature and high humidity environments, and due to the toxicity of antimony elements, the industry has urgent demand for research on antimony-free cable materials.

Method used

The combination of chlorinated polyethylene and polyethylene is used to combine with butadiene-based polymer, and the composite of alkenyl ring triphosphazene with white carbon black, aluminum silicate and antimony-free flame retardant is formed to form a collaborative flame retardant system to construct a multi-dimensional crosslinking network structure.

Benefits of technology

The excellent performance of antimony-free fire-resistant flame-retardant cable materials in high temperature and high humidity environments is achieved, including high tensile strength, elongation of break, high temperature resistance and humidity resistance stability, which significantly improves the safety of cable materials use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220010940000031
    Figure BDA0005220010940000031
  • Figure BDA0005220010940000061
    Figure BDA0005220010940000061
  • Figure BDA0005220010940000071
    Figure BDA0005220010940000071
Patent Text Reader

Abstract

The invention provides an antimony-free fireproof flame-retardant cable material as well as a preparation method and application thereof, and the antimony-free fireproof flame-retardant cable material is prepared from the following raw materials in parts by mass: 35 to 60 parts of chlorinated polyethylene, 1 to 15 parts of polyethylene, 0.5 to 8 parts of butadiene-based polymer, 2 to 20 parts of alkenyl cyclotriphosphazene, 5 to 20 parts of white carbon black and 5 to 30 parts of aluminum silicate. 10-40 parts of an antimony-free flame retardant, 0.1-3 parts of a cross-linking agent and 0.1-4 parts of an assistant cross-linking agent. Through design and mutual compounding of all the components, the antimony-free fireproof and flame-retardant cable material has excellent fireproof and flame-retardant effects, and the use safety of the cable material is remarkably improved; meanwhile, the antimony-free fireproof flame-retardant cable material has excellent mechanical properties, oil resistance, high-temperature-resistant stability and damp-heat-resistant stability, and meets the requirements of continuous, safe and stable operation of the cable material in severe environments such as high temperature and high humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to an antimony-free fire-retardant cable material and a preparation method and application thereof. Background Art

[0002] The performance of wires and cables directly determines the operating level of electrical equipment and power systems, and they are indispensable products in people's lives. Traditional insulated cables are mainly divided into the following categories according to their formulas: natural styrene-butadiene rubber, EPDM rubber, chlorinated polyethylene, etc. Among them, chlorinated polyethylene is a polymer material made from high-density polyethylene (HDPE) through chlorination substitution reaction, which has excellent weather resistance, ozone resistance, chemical resistance, oil resistance and coloring performance; at the same time, because its molecular structure contains chlorine elements, it also has good performance in flame retardancy, so it is one of the most commonly used materials in insulated cables.

[0003] CN105237896A discloses a chlorinated polyethylene rubber sheath for charging pile cables, which is prepared from the following raw materials: 100 parts of chlorinated polyethylene resin, 1-2 parts of calcium stearate, 0.3-0.6 parts of stearic acid, 10-20 parts of magnesium oxide, 4-8 parts of crude paraffin, 25-35 parts of composite flame retardant, 20-30 parts of white carbon black, 5-7 parts of antimony trioxide, 40-50 parts of chlorinated paraffin, 2-4 parts of diisopropylbenzene peroxide, 2-3 parts of triallyl isocyanurate, 0.4-1 parts of A-172 silane coupling agent, 1.2-2 parts of permanent yellow, 0.4-0.8 parts of permanent red, and 2-3 parts of titanium dioxide. The orange-red chlorinated polyethylene rubber produced using this formula has high tensile strength and elongation, excellent acid and alkali corrosion resistance and flame retardant properties, can meet the use requirements of charging pile cables, and is cheap.

[0004] CN103589101A discloses an environmentally friendly flame-retardant and low-temperature resistant chlorinated polyethylene rubber material for wind power cables. The raw materials are as follows: 95-105 parts of chlorinated polyethylene rubber, 5-15 parts of modifier, 8-10 parts of magnesium oxide, 3-5 parts of calcium zinc stabilizer, 1-1.5 parts of antioxidant, 0.5-1 part of stearic acid, 7-10 parts of antimony trioxide, 2-3 parts of semi-refined paraffin, 15-20 parts of pigment carbon black, 30-35 parts of precipitated white carbon black, 12-18 parts of environmentally friendly composite flame retardant, 25-35 parts of talc, 5-7 parts of auxiliary cross-linking agent, 4-6 parts of peroxide cross-linking agent, 18-20 parts of plasticizer, and 8-12 parts of plasticizer dioctyl adipate. The wind power cable prepared by using the rubber material has good flame retardancy, torsion resistance, low temperature resistance and flexibility.

[0005] CN104761838A discloses a chlorinated polyethylene rubber, the raw materials of which are as follows: 25-45% chlorinated polyethylene, 5-15% chlorosulfonated polyethylene, 10-30% reinforcing agent, 5-15% plasticizer, 5-10% flame retardant, 0.5-1% antioxidant, 5-10% nano-montmorillonite, 0.5-2% sensitizer, 1-5% active agent, and 0.1-0.5% coupling agent. The chlorinated polyethylene rubber has good flame retardancy and wear resistance, and also has excellent tensile strength and tear resistance.

[0006] The flame retardants commonly used in cable materials in the industry include metal hydroxides, halogen flame retardants, antimony flame retardants, etc. Halogen flame retardants are gradually withdrawing from the market because they do not meet environmental protection requirements. Antimony flame retardants have the advantages of low price and good flame retardant effect, but antimony compounds themselves have certain toxicity. In recent years, major environmental protection organizations have begun to limit the antimony content in controlled products. Therefore, antimony-free cable materials have become an important research topic at present. In the face of halogen-free and antimony-free requirements, the industry uses metal hydroxides such as magnesium hydroxide and aluminum hydroxide for flame retardancy. Such flame retardants need to be added in large amounts to exert better fire retardant effects, but adding a large amount of flame retardants will cause the mechanical properties, high temperature resistance and moisture and heat resistance of cable materials to drop significantly, especially in high temperature and high humidity environments, it is impossible to maintain stable operation.

[0007] Therefore, the development of environmentally friendly fire-retardant cable materials with excellent mechanical properties, high temperature resistance and moisture and heat resistance is a research focus in this field. Summary of the invention

[0008] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an antimony-free fire-retardant cable material and a preparation method and application thereof. Through the design and mutual compounding of each component, the antimony-free fire-retardant cable material can achieve excellent fire-retardant effects while having excellent mechanical properties, oil resistance, high temperature stability and moisture and heat stability, thereby meeting the needs of continuous, safe and stable operation of cable materials in harsh environments such as high temperature and high humidity.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an antimony-free fire-retardant cable material, wherein the raw materials for preparing the antimony-free fire-retardant cable material include the following components in parts by mass:

[0011]

[0012] In the antimony-free fire-retardant cable material provided by the present invention, a combination of chlorinated polyethylene (CPE) and polyethylene (PE) is used as the main material and compounded with a butadiene-based polymer. It can undergo a vulcanization cross-linking reaction with a cross-linking agent and an auxiliary cross-linking agent to form a dense and stable cross-linked network in the cable material, thereby improving its mechanical properties, high temperature stability and moisture and heat resistance stability.

[0013] Furthermore, the present invention adopts alkenyl cyclotriphosphazene as a reactive nitrogen-phosphorus flame retardant, which is compounded with white carbon black, aluminum silicate and antimony-free flame retardant to form a composite flame retardant system, and synergistically exerts excellent fire retardant performance; on the other hand, the alkenyl functional group in the alkenyl cyclotriphosphazene undergoes a cross-linking reaction of a free radical mechanism with an organic system (including CPE, PE, butadiene polymer, cross-linking agent, and auxiliary cross-linking agent), and the cyclotriphosphazene structure is embedded in the cross-linking network in the form of a covalent bond, so that the cable material achieves intrinsic flame retardancy, and at the same time, a multidimensional cross-linking network containing carbon-carbon bonds and nitrogen-phosphorus rings is constructed, which effectively improves the mechanical properties, high temperature stability and wet heat stability of the cable material.

[0014] Therefore, the present invention constructs a synergistic flame retardant system through the design and mutual compounding of each component, and forms a specific multi-dimensional cross-linked network structure in the material, so that the antimony-free fire-retardant cable material has excellent fire-retardant and flame-retardant effects, especially has an extremely low burn loss rate in continuous combustion, which significantly improves the safety of use; at the same time, the antimony-free fire-retardant cable material has high tensile strength and elongation at break, excellent mechanical properties, high temperature stability, moisture and heat stability and oil resistance, which meets the needs of continuous, safe and stable operation of cable materials in harsh environments such as high temperature and high humidity.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] In the preparation raw materials of the present invention, the mass parts of the chlorinated polyethylene are 35-60 parts, for example, 38 parts, 40 parts, 42 parts, 45 parts, 48 ​​parts, 50 parts, 52 parts, 55 parts or 58 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] The mass proportion of the polyethylene is 1-15 parts, for example, it can be 2 parts, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts or 14 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0018] The mass fraction of the butadiene-based polymer is 0.5-8 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts or 7 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0019] The mass fraction of the alkenyl cyclotriphosphazene is 2-20 parts, for example, 3 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0020] The mass proportion of the white carbon black is 5-20 parts, for example, it can be 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0021] The mass proportion of the aluminum silicate is 5-30 parts, for example, it can be 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts or 28 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0022] The mass parts of the antimony-free flame retardant are 10-40 parts, for example, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts or 38 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0023] The mass fraction of the cross-linking agent is 0.1-3 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0024] The weight percentage of the auxiliary cross-linking agent is 0.1-4 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts or 3.8 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0025] In the present invention, the chlorinated polyethylene (CPE) is CPE resin and / or CPE rubber, preferably CPE rubber.

[0026] Preferably, the chlorine content in the chlorinated polyethylene is 25-40wt%, for example, it can be 28wt%, 30wt%, 32wt%, 34wt%, 35wt%, 36wt% or 38wt%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0027] Preferably, the polyethylene includes any one of linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), and metallocene polyethylene, or a combination of at least two thereof, and a combination of high-density polyethylene and metallocene polyethylene is further preferred.

[0028] As a preferred technical solution of the present invention, the polyethylene includes a combination of HDPE and metallocene polyethylene, HDPE has high hardness, tensile strength and toughness; metallocene polyethylene is a linear polyethylene prepared by catalysis using a metallocene (MAO) catalyst, has a narrow molecular weight distribution, a regular molecular chain structure, and a large elongation at break. The compounding of HDPE and metallocene polyethylene, and the combination with CPE, can improve the mechanical properties and wear resistance of the antimony-free fire-retardant cable material.

[0029] Preferably, the mass ratio of the high-density polyethylene to the metallocene polyethylene is (0.8-2):1, for example, it can be 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 1.9:1, etc.

[0030] Preferably, the butadiene-based polymer comprises polybutadiene and / or butadiene-styrene copolymer.

[0031] Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000, for example, it may be 2000, 3000, 4000, 5000, 6000, 7000, 8000 or 9000, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Preferably, the butadiene-based polymer comprises a structural unit represented by formula I:

[0033]

[0034] In the present invention, the butadiene-based polymer contains the 1,2-vinyl structural unit shown in Formula I, and the vinyl in the side chain has a high reactivity, and can undergo a vulcanization cross-linking reaction with a co-cross-linking agent, chlorinated polyethylene, polyethylene, and alkenyl cyclotriphosphazene under the action of a cross-linking agent, so as to form a specific multi-dimensional cross-linked network structure in the cable material, so that the antimony-free fire-retardant cable material has excellent mechanical properties, high temperature resistance, and wet heat resistance. If the butadiene-based polymer does not contain the 1,2-vinyl structural unit shown in Formula I, its reactivity is insufficient, resulting in a decrease in the cross-linking degree of the cable material, thereby reducing the mechanical properties, high temperature stability, and wet heat resistance stability.

[0035] Preferably, the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-90%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 52%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 88%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0036] Preferably, the alkenyl cyclotriphosphazene has a structure as shown in Formula II:

[0037]

[0038] In Formula II, R1, R2, R3, R4, R5, and R6 are each independently selected from unsubstituted or R'-substituted phenyl, Any one of, and at least one (e.g., 2, 3, 4, 5, 6) of R1, R2, R3, R4, R5 and R6 is -* indicates the attachment site of the group.

[0039] R' is selected from any one of halogen, C1-C6 straight chain or branched alkyl, C1-C6 alkoxy, and phenyl.

[0040] R is selected from any one of C2-C10 alkenyl groups.

[0041] n represents the number of groups R, and is an integer selected from 1-5, for example, 1, 2, 3, 4 or 5. It should be noted that when n≥2, multiple R are the same or different groups. Preferably, n is 1.

[0042] In the present invention, the C2-C10 alkenyl group may be a straight chain or branched alkenyl group of C2, C3, C4, C5, C6, C7, C8, C9, or C10, containing at least one C=C, illustratively including but not limited to vinyl, propenyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, butadienyl, pentadienyl, and the like.

[0043] The halogen includes F, Cl, Br, and I.

[0044] The C1-C6 straight chain or branched alkyl group can be a straight chain or branched alkyl group of C1, C2, C3, C4, C5, or C6, and illustratively includes but is not limited to: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, sec-butyl, n-pentyl, tert-pentyl, isopentyl, tert-pentyl, hexyl, and the like.

[0045] The C1-C6 alkoxy group may be a C1, C2, C3, C4, C5, or C6 alkoxy group, and a specific example thereof is a monovalent group formed by connecting the aforementioned straight-chain or branched alkyl group to O.

[0046] Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is

[0047] Among the R1, R2, R3, R4, R5 and R6 The number is 1-6, such as 1, 2, 3, 4, 5 or 6, preferably 2-6.

[0048] Preferably, the R is selected from vinyl, propenyl or allyl.

[0049] Preferably, the silica includes fumed silica and / or precipitated silica.

[0050] Preferably, the particle size of the white carbon black is 5-300nm, for example, it can be 10nm, 20nm, 50nm, 60nm, 80nm, 100nm, 120nm, 140nm, 150nm, 160nm, 180nm, 200nm, 220nm, 250nm or 280nm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0051] Preferably, the particle size of the aluminum silicate is 0.01-50 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Preferably, the antimony-free flame retardant includes any one of aluminum hydroxide, magnesium hydroxide, zinc borate, and zinc stannate, or a combination of at least two thereof, and a combination of aluminum hydroxide and zinc borate is further preferred.

[0053] As a preferred technical solution of the present invention, the antimony-free flame retardant includes a combination of aluminum hydroxide and zinc borate, which is compounded with alkenyl cyclotriphosphazene, white carbon black and aluminum silicate to form a synergistic flame retardant system, which can form a dense protective layer during combustion to prevent the escape of internal gas and block the entry of external oxygen, thereby significantly improving the flame retardant properties of the antimony-free fire-retardant cable material, and can have an extremely low burn loss rate during continuous combustion, greatly improving the safety of the cable material.

[0054] Preferably, the mass ratio of the aluminum hydroxide to the zinc borate is (1.5-4):1, for example, it can be 1.6:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, etc.

[0055] Preferably, the cross-linking agent comprises an organic peroxide, and further preferably any one or a combination of at least two of diisopropylbenzene hydroperoxide, dibenzoyl peroxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di(4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, cyclohexanone peroxide, and tert-butyl peroxy-3,5,5-trimethylhexanoate.

[0056] Preferably, the auxiliary cross-linking agent is a compound containing at least 2 (≥2, such as 2, 3, 4, 5, 6, etc.) unsaturated groups (such as alkenyl groups).

[0057] Preferably, the auxiliary cross-linking agent includes any one of pentaerythritol triacrylate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, and propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.

[0058] Preferably, the preparation raw materials also include 0.5-5 parts of compatibilizer by mass, and the mass parts of the compatibilizer can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene propylene diene monomer rubber, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof.

[0060] Preferably, the preparation raw materials also include 0.5-5 parts of plasticizer by mass, and the mass parts of the plasticizer can be 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0061] Preferably, the plasticizer includes any one of dioctyl adipate, dioctyl phthalate, diisodecyl phthalate, and dioctyl terephthalate, or a combination of at least two of them.

[0062] Preferably, the preparation raw materials further include any one of a lubricant, a silane coupling agent, a stabilizer, an ultraviolet absorber, and an antioxidant, or a combination of at least two thereof.

[0063] Preferably, the preparation raw material also includes 0.1-3 parts of lubricant by mass, and the mass proportion of the lubricant can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0064] Preferably, the lubricant includes any one of silicone powder, silicone masterbatch, polyethylene wax, or a combination of at least two of them.

[0065] Preferably, the preparation raw materials also include 0.1-3 parts of stabilizer by mass, and the mass parts of the stabilizer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts or 2.8 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0066] Preferably, the stabilizer includes any one of zinc stearate, calcium stearate, magnesium stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) or a combination of at least two thereof.

[0067] Preferably, the preparation raw materials further include 0.1-2 parts by mass of a silane coupling agent, and the mass parts of the silane coupling agent can be 0.2 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0068] Preferably, the silane coupling agent includes any one of an alkenyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof.

[0069] Further preferably, the silane coupling agent includes any one of vinyltriethoxysilane, vinyltrimethoxysilane, γ-(methacryloxy)propyltrimethoxysilane, methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of at least two thereof.

[0070] Preferably, the preparation raw materials further include 0.1-1.5 parts of antioxidants by mass, and the mass parts of the antioxidants can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts or 1.4 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0071] Preferably, the antioxidant includes any one of a hindered phenol antioxidant, a hindered amine antioxidant, and a phosphite antioxidant, or a combination of at least two thereof.

[0072] Preferably, the preparation raw materials further include 0.1-1.5 parts of ultraviolet absorbers in parts by mass, and the mass parts of the ultraviolet absorbers can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.8 parts, 1 parts, 1.2 parts or 1.4 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0073] In a second aspect, the present invention provides a method for preparing the antimony-free fire-retardant cable material as described in the first aspect, the preparation method comprising:

[0074] The prepared raw materials are mixed and extruded to obtain pellets;

[0075] The pellets are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the antimony-free fire-retardant cable material.

[0076] Preferably, the mixing is carried out in an internal mixer.

[0077] Preferably, the mixing temperature is 150-180°C, for example, it can be 155°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, 175°C or 178°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0078] Preferably, the mixing time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0079] Preferably, the extrusion granulation is carried out in a screw extruder, such as a single-screw extruder or a twin-screw extruder.

[0080] Preferably, the operating temperature of the screw extruder is 100-165°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or 160°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0081] Preferably, the screw extruder comprises a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone and a seventh zone connected in sequence, and the temperature of each zone is independently 105-165°C, for example, it can be 108°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or 160°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0082] Preferably, the temperature of the first zone in the screw extruder is 105-110°C (e.g., 106°C, 107°C, 108°C, 109°C, etc.), the temperature of the second zone is 115-140°C (e.g., 116°C, 118°C, 120°C, 122°C, 125°C, 128°C, 130°C, 132°C, 135°C or 138°C, etc.), the temperature of the third zone is 120-150°C (e.g., 122°C, 125°C, 128°C, 130°C, 132°C, 135°C, 138°C, 140°C, 142°C, 145°C or 148°C, etc.), and the temperature of the fourth zone is 120-150°C (e.g., 122°C, 125°C, 128°C, 130°C, 132°C, 135°C or 148°C, etc.). ℃, 138℃, 140℃, 142℃, 145℃ or 148℃, etc.), the temperature of the fifth zone is 120-150℃ (for example, 122℃, 125℃, 128℃, 130℃, 132℃, 135℃, 138℃, 140℃, 142℃, 145℃ or 148℃, etc.), the temperature of the sixth zone is 120-150℃ (for example, 122℃, 125℃, 128℃, 130℃, 132℃, 135℃, 138℃, 140℃, 142℃, 145℃ or 148℃, etc.), and the temperature of the seventh zone is 125-150℃ (for example, 128℃, 130℃, 132℃, 135℃, 138℃, 140℃, 142℃, 145℃ or 148℃, etc.).

[0083] Preferably, the operating temperature of the wire extruder is 110-180°C, for example, it can be 115°C, 120°C, 125°C, 130°C, 140°C, 150°C, 160°C, 170°C or 175°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0084] Preferably, the wire extruder comprises a zone A, a zone B, a zone C and a zone D connected in sequence, so that the pellets can pass through the zones A, B, C and D in sequence, wherein the operating temperature of the zone A is 120-150°C (e.g., 122°C, 125°C, 128°C, 130°C, 132°C, 135°C, 138°C, 140°C, 142°C, 145°C, 148°C, etc.), and the operating temperature of the zone B is 140-175°C (e.g., 142°C, 145°C, 148°C, 150°C, 152°C, 155°C, 158°C, 160°C, 162°C, 165°C, etc.). , 168°C, 170°C, 172°C, etc.), the operating temperature of zone C is 140-175°C (for example, 142°C, 145°C, 148°C, 150°C, 152°C, 155°C, 158°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, etc.), and the operating temperature of zone D is 140-180°C (for example, 142°C, 145°C, 148°C, 150°C, 152°C, 155°C, 158°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C, etc.).

[0085] Preferably, the dose of the radiation cross-linking is 2-12 Mrad, for example, it can be 2.5 Mrad, 3 Mrad, 3.5 Mrad, 4 Mrad, 4.5 Mrad, 5 Mrad, 5.5 Mrad, 6 Mrad, 6.5 Mrad, 7 Mrad, 7.5 Mrad, 8 Mrad, 8.5 Mrad, 9 Mrad, 9.5 Mrad, 10 Mrad or 11 Mra, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0086] In a third aspect, the present invention provides an application of the antimony-free fire-retardant cable material as described in the first aspect in electrical wires, building cables, wind power generation devices or solar power generation devices.

[0087] Compared with the prior art, the present invention has the following beneficial effects:

[0088] (1) In the antimony-free fire-retardant cable material provided by the present invention, a synergistic fire-retardant system is constructed by designing and compounding each component, and a covalent cross-linking system comprising components such as chlorinated polyethylene, polyethylene, butadiene-based polymer, alkenyl cyclotriphosphazene, cross-linking agent and co-cross-linking agent is constructed, forming a specific multi-dimensional cross-linked network structure in the cable material, so that the antimony-free fire-retardant cable material has excellent fire-retardant effect, has an extremely low burn loss rate during continuous combustion, and significantly improves the safety of the cable material; at the same time, the antimony-free fire-retardant cable material has excellent mechanical properties, oil resistance, high temperature stability and moisture and heat stability, which meets the needs of continuous safe and stable operation of cable materials in harsh environments such as high temperature and high humidity.

[0089] (2) The present invention, through the design and optimization of components, enables the antimony-free fire-retardant cable material to achieve VW-1 grade flame retardancy, with a burn loss rate of ≤20% after 60 minutes of continuous burning, a tensile strength of ≥15.5 MPa, an elongation at break of ≥420%, a change rate of elongation at break after aging at 185°C for 168 hours of ≤7%, a change rate of elongation at break after double 85 test for 240 hours of ≤10%, and a change rate of elongation at break after oil immersion at 100°C for 24 hours of ≤5%. The material has excellent comprehensive performance in terms of fire retardancy, mechanical properties, high temperature stability, oil resistance, moisture and heat stability, and safety in use. DETAILED DESCRIPTION

[0090] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0091] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0092] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.

[0093] In the following specific embodiments of the present invention, the materials for which the preparation methods are not provided are all commercially available chemicals, and the specific information is as follows:

[0094]

[0095]

[0096]

[0097] The following will take multiple embodiments as examples to describe in detail the antimony-free fire-retardant cable material and the preparation method thereof of the present invention, but the antimony-free fire-retardant cable material and the preparation method thereof of the present invention are not limited to these embodiments.

[0098] Examples 1-8, Comparative Examples 1-7

[0099] An antimony-free fire-retardant cable material, the raw materials for its preparation are shown in Table 1 and Table 2, and the dosage unit of each component is "part".

[0100] The preparation method of the antimony-free fire-retardant cable material is as follows:

[0101] (1) adding each component into a mixer according to the formula amount, premixing for 3 minutes to obtain a mixture; adding the mixture into an internal mixer, mixing at 160° C. for 25 minutes, and extruding and granulating through a single screw extruder to obtain pellets; the operating temperatures of zones 1 to 7 in the single screw extruder are 110° C., 115° C., 115° C., 120° C., 120° C., 120° C., and 125° C., respectively.

[0102] (2) adding the pellets obtained in step (1) into a wire extruder and extruding to obtain wires, wherein the operating temperatures of the AD zone in the wire extruder are 130° C., 150° C., 150° C., and 165° C., respectively; irradiating and cross-linking the wires through an electron accelerator, wherein the irradiation dose is 4 Mrad, to obtain the antimony-free fire-retardant cable material.

[0103] The following performance tests are conducted on antimony-free fire-retardant cable materials:

[0104] (1) Vertical burning test: The test is conducted in accordance with the method in standard UL 1581.

[0105] (2) Burning rate: Use an alcohol burner with a flame height of 120 mm and a heat power of 500 W. Burn the sample at a 45° angle for 60 min. Calculate the mass change rate before and after combustion, which is the burning rate.

[0106] (3) Tensile strength and elongation at break: tested according to the method in standard GB / T 2951.11-2008.

[0107] (4) Heat resistance: After the cable material to be tested is aged at 185°C for 168 h, its elongation at break is tested and compared with the elongation at break measured in (3) to obtain the rate of change; rate of change = difference in elongation at break before and after aging / original test value.

[0108] (5) Moisture and heat resistance: The cable material to be tested is placed in a moisture and heat aging test chamber at 85°C and 85% humidity. After 240 hours, the elongation at break is tested and compared with the elongation at break measured in (3) to obtain the rate of change; rate of change = difference in elongation at break before and after moisture and heat aging / original test value.

[0109] (6) Oil resistance: The cable material to be tested is immersed in mineral oil. After 24 h at 100°C, its elongation at break is measured and compared with the elongation at break measured in (3) to obtain the rate of change; rate of change = difference in elongation at break before and after oil immersion / original test value.

[0110] The test results are shown in Table 1 and Table 2.

[0111] Table 1

[0112]

[0113]

[0114]

[0115] Table 2

[0116]

[0117]

[0118] According to the data in Table 1, the present invention constructs a synergistic fire retardant system through the design and mutual compounding of each component, and forms a specific multi-dimensional cross-linked network structure in the cable material, so that the antimony-free fire retardant cable material has excellent fire retardant properties, mechanical properties, oil resistance, high temperature stability and wet heat stability. Among them, the cable material of Examples 1-6 can achieve VW-1 flame retardancy, the burn loss rate of 60min continuous burning is 18.1-19.8%, the tensile strength is 15.5-16.0MPa, the elongation at break is 420-441%, the elongation at break after aging at 185°C for 168h is 6.2-6.9%, the elongation at break after double 85 test for 240h is 8.7-9.6%, and the elongation at break after immersion in oil at 100°C for 24h is 4.1-4.9%, which has excellent comprehensive performance.

[0119] The present invention adopts aluminum hydroxide, zinc borate, aluminum silicate, white carbon black and alkenyl cyclotriphosphazene to jointly construct a synergistic fire retardant system. Through the design and optimization of the dosage of each component, the cable material can achieve the improvement of the comprehensive effects of flame retardancy, mechanical properties, heat resistance, and resistance to moisture and heat. The dosage ratio of aluminum hydroxide and zinc borate in Examples 7-8 exceeds the further preferred range of the present invention, resulting in an increase in the 60min burn rate and a slight decrease in fire resistance. The dosage of aluminum silicate and white carbon black in Comparative Examples 6-7 exceeds the limited range of the present invention, resulting in a significant decrease in the flame retardancy of the cable material and a substantial increase in the 60min burn rate. Comparative Example 1 does not contain alkenyl cyclotriphosphazene, which not only brings about a decrease in flame retardant and fireproof properties, but also changes the cross-linked structure of the cable material, and the mechanical properties, oil resistance, heat resistance, and resistance to moisture and heat are comprehensively deteriorated. The cyclotriphosphazene in Comparative Example 2 is not reactive and exists only as an additive nitrogen-phosphorus flame retardant in the cable material. Although its fire retardant properties are slightly improved compared with Comparative Example 1, due to insufficient crosslinking in the system, its mechanical properties, oil resistance, heat resistance and moisture-heat resistance are poor.

[0120] The present invention constructs a covalent cross-linking system in which chlorinated polyethylene, polyethylene, butadiene-based polymer, alkenyl cyclotriphosphazene, cross-linking agent and auxiliary cross-linking agent act together through the design and mutual compounding of each component, and has a specific multi-dimensional cross-linking network structure in the cable material, so that it has excellent flame retardancy, mechanical properties, heat resistance, oil resistance and wet heat resistance. Comparative Example 3 does not contain a butadiene-based polymer, and Comparative Example 5 contains hydrogenated SEBS. Since the system does not contain a reactive side chain vinyl, the cross-linking degree of the cable material is reduced, resulting in a significant reduction in its mechanical properties, oil resistance, heat resistance, and wet heat aging resistance. In Comparative Example 4, the amount of butadiene-based polymer used is too much, resulting in a significant decrease in the flexibility of the cable material and a brittle phenomenon.

[0121] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the antimony-free fire-retardant cable material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An antimony-free fire-retardant cable material, characterized in that: The raw materials for preparing the antimony-free fire-retardant cable material include the following components by weight:

2. The antimony-free fire-retardant cable material according to claim 1, characterized in that: The polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof; Preferably, the butadiene-based polymer comprises polybutadiene and / or butadiene-styrene copolymer; Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000; Preferably, the butadiene-based polymer comprises a structural unit represented by formula I, and the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-90%; 3. The antimony-free fire-retardant cable material according to claim 1 or 2, characterized in that: The alkenyl cyclotriphosphazene has a structure as shown in Formula II: Wherein, R1, R2, R3, R4, R5, and R6 are each independently selected from unsubstituted or R'-substituted phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is -* indicates the attachment site of the group; R' is selected from any one of halogen, C1-C6 straight or branched alkyl, C1-C6 alkoxy, and phenyl; R is selected from any one of C2-C10 alkenyl groups; n is an integer selected from 1 to 5; Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is Preferably, the R is selected from vinyl, propenyl or allyl.

4. The antimony-free fire-retardant cable material according to any one of claims 1 to 3, characterized in that: The particle size of the white carbon black is 5-300nm; Preferably, the particle size of the aluminum silicate is 0.01-50 μm; Preferably, the antimony-free flame retardant comprises any one of aluminum hydroxide, magnesium hydroxide, zinc borate, and zinc stannate, or a combination of at least two thereof, and a combination of aluminum hydroxide and zinc borate is further preferred; Preferably, the mass ratio of the aluminum hydroxide to the zinc borate is (1.5-4):

1.

5. The antimony-free fire-retardant cable material according to any one of claims 1 to 4, characterized in that: The cross-linking agent includes an organic peroxide, preferably any one of diisopropylbenzene hydroperoxide, dibenzoyl peroxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxybenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di (4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, cyclohexanone peroxide, tert-butyl peroxy-3,5,5-trimethylhexanoate or a combination of at least two thereof; Preferably, the auxiliary cross-linking agent includes any one of pentaerythritol triacrylate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, and propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.

6. The antimony-free fire-retardant cable material according to any one of claims 1 to 5, characterized in that: The raw materials for preparation further include 0.5-5 parts of a compatibilizer by weight; Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, maleic anhydride grafted ethylene propylene diene monomer rubber, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.5-5 parts by weight of a plasticizer; Preferably, the plasticizer includes any one of dioctyl adipate, dioctyl phthalate, diisodecyl phthalate, and dioctyl terephthalate, or a combination of at least two of them.

7. The antimony-free fire-retardant cable material according to any one of claims 1 to 6, characterized in that: The preparation raw materials also include any one or a combination of at least two of lubricants, silane coupling agents, stabilizers, ultraviolet absorbers, and antioxidants; Preferably, the raw material for preparation further comprises 0.1-3 parts by mass of lubricant; Preferably, the lubricant comprises any one of silicone powder, silicone masterbatch, polyethylene wax, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-3 parts of a stabilizer by weight; Preferably, the stabilizer includes any one of zinc stearate, calcium stearate, magnesium stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-2 parts by mass of a silane coupling agent; Preferably, the silane coupling agent includes any one of an alkenyl silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-1.5 parts by mass of an antioxidant.

8. A method for preparing the antimony-free fire-retardant cable material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The prepared raw materials are mixed and extruded to obtain pellets; The pellets are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the antimony-free fire-retardant cable material.

9. The preparation method according to claim 8, characterized in that: The mixing temperature is 150-180°C; Preferably, the mixing time is 5-30 min; Preferably, the extrusion granulation is carried out in a screw extruder; Preferably, the operating temperature of the screw extruder is 100-150°C; Preferably, the working temperature of the wire extruder is 110-180°C; Preferably, the radiation cross-linking dosage is 2-12 Mrad.

10. Use of the antimony-free fire-retardant cable material according to any one of claims 1 to 7 in electrical wires, building cables, wind power generation devices or solar power generation devices.

Citation Information

Patent Citations

  • Chlorinated polyethylene rubber for environment-friendly, flame-retardant and low-temperature-resistant wind energy cable, and preparation method

    CN103589101A

  • Chlorinated polyethylene rubber and preparation method thereof

    CN104761838A

  • Chlorinated polyethylene rubber sheath special for charging pile cable and preparation method thereof

    CN105237896A